Temporary or sustainable? Strategic and leadership perspectives on the four-day work week - Fontes, A.; Pereira, L. F.; Dias, Á. (International Journal of Organizational Analysis)
Purpose This study aims to investigate whether the four-day work week (4DWW) can function not merely as a human resource policy but as a strategic organizational resource capable of creating sustainable competitive advantage. Addressing a key gap in the literature, it explores the four-day week from a strategic and leadership perspective, contrasting with prior research that has focused primarily on employee well-being and productivity outcomes. Design/methodology/approach The study applies the resource-based view (RBV) and the valuable, rare, inimitable and organizationally (VRIO) framework to assess the strategic value, rarity, inimitability and organizational feasibility of this work arrangement. A qualitative design was adopted, based on 20 semi-structured interviews with chief executive officers, managers and directors. Interview data were analyzed using text-mining tools to identify dominant patterns and themes aligned with VRIO dimensions. Findings Results reveal divided managerial perceptions: the policy is widely perceived as valuable and rare, but less consistently inimitable or organizationally feasible. This indicates that, in its current stage, the 4DWW represents a temporary competitive advantage with potential to evolve into a sustainable one as organizational capabilities mature. Research limitations/implications The research is limited by its single-country sample (Portugal), the early stage of policy adoption and the lack of cross-sectoral comparison. Future research could integrate employee perspectives and quantitative performance indicators to strengthen empirical generalization. Practical implications The findings suggest that leadership commitment, communication and strategic alignment are essential for the successful implementation of the 4DWW. Organizations that embed the policy within broader strategic and cultural frameworks may enhance talent attraction, retention and innovation capacity while differentiating themselves in competitive markets. Social implications Leadership-driven adoption of reduced working time can support employee well-being, inclusion and gender equality, while promoting healthier work–life integration. However, attention must be given to workload management and sectoral adaptability to prevent unintended inequalities. Originility/value This study fills a theoretical and empirical gap by applying the VRIO framework to the 4DWW and reframing it as an intangible strategic resource shaped by leadership behavior and organizational design. It contributes to the literature by linking strategic management and leadership theory with emerging debates on work-time reduction and sustainable competitiveness.